2019
DOI: 10.1155/2019/7382717
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Study of the Antibacterial Chitosan/Polyvinyl Alcohol Loaded with Silver Nanoparticle Hydrogel for Wound Healing Applications

Abstract: Silver nanoparticles have attracted great interests widely in medicine due to its great characteristics of antibacterial activity. In this research, the antibacterial activity and biocompatibility of a topical gel synthesized from polyvinyl alcohol, chitosan, and silver nanoparticles were studied. Hydrogels with different concentrations of silver nanoparticles (15 ppm, 30 ppm, and 60 ppm) were evaluated to compare their antibacterial activity, nanoparticles’ sizes, and in vivo behaviors. The resulted silver na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…Nguyen et al reported hydrogel composed of chitosan, polyvinyl alcohol, and loaded with silver nanoparticles. The hydrogel excellent antibacterial activity was against P. aeruginosa and S. aureus [ 83 ]. Chen et al developed carboxymethyl chitosan-based hydrogels loaded with melatonin.…”
Section: Preparation Techniques and Properties Of Hydrogelsmentioning
confidence: 99%
“…Nguyen et al reported hydrogel composed of chitosan, polyvinyl alcohol, and loaded with silver nanoparticles. The hydrogel excellent antibacterial activity was against P. aeruginosa and S. aureus [ 83 ]. Chen et al developed carboxymethyl chitosan-based hydrogels loaded with melatonin.…”
Section: Preparation Techniques and Properties Of Hydrogelsmentioning
confidence: 99%
“…When the CG was dipped in the DA solution in a mild alkaline and oxygen-rich environment, the DA polymerised to form a thin adherent layer of PDA on the CG surface. When immersed in silver nitrate solution, the incompletely oxidized active groups such as catechol and amine functional groups, presenting in the PDA layer reduced the silver ions into a surface-bound metallic Ag 8,18. Two hydroxyl groups in the ortho positions on the PDA layer were likely involved in a reaction whereby the dihydroxyl molecules lost two-electrons to form a quinone structure and stabilise the newly formed Ag 30,31…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, cotton gauze (CG) was chosen as the model dressing material. In the first step, we used the PDA-assisted reduction and immobilisation chemistry to immobilize Ag from silver nitrate solution 8,14,15. A number of studies have shown that dopamine auto-oxidation (at an alkaline pH above 8) can coat a layer of nanometre thick (~less than 5 nm) PDA on substrate chemistries such as metals, ceramics, and polymers 1618.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, bioinspired silver nanoparticles (AgNPs) have been a research focus due to the increasing need for AgNPs and the utmost advantages of green synthesis. AgNPs have been applied extensively in many fields, such as biomedical, medicine, cosmetic, food preservation, catalysis, sunscreen, and textile industries [1][2][3][4]. Green synthesis has gained more attention than physical and chemical methods due to a number of reasons: the use of clean and nontoxic chemicals and renewable materials; the use of environmentally benign solvents as the aqueous media of the reaction; simplicity; and low cost [5][6][7].…”
Section: Introductionmentioning
confidence: 99%